AN ORIGINAL APPROACH TO REGIMENTAL HISTORY: THE STORY OF THE WITWATERSRAND RIFLES - Monick, S. (Scientia Militaria - South African Journal of Military Studies, 2012)
At the end of October 1989 the regimental history of the Witwatersrand Rifles was published. The book is entitled A bugle calls: the story of the Witwatersrand Rifles and its predecessors 1899-1987, and its 764 pages (which includes some 65 maps and 105 photographs) details the history of this Citizen Force regiment, headquartered at Germiston, on the East Rand (since 1963). The author, Dr S Monick (a senior professional officer at the South African National Museum of Military History, in Johannesburg) has adopted what he hopes is a unique and refreshingly original approach to regimental history specifically, and South African military history in general. The following article is not, of course, a review of the book; such an object demands the highest degree of objectivity which is, obviously, impossible in this paper written by the author of the book himself. Rather, what is intended is a critique of the approach and methodology adopted in the regimental history.